The Effect of Covid-19 Volunteer Motivation on Affective Commitment Through Volunteer Satisfaction - Immanuel Mu'ammal; Arief Nur Rahman (Peradaban Journal of Economic and Business, 2023)
The COVID-19 pandemic has led to a huge wave of compassion. In particular, volunteering platforms established channelling help for high-risk groups. Volunteers have become a valuable set of human resources in many sectors of society. This study focuses on the research on the effect of volunteer motivation involved on affective commitment of members mediated volunteer satisfaction in work. This research was conducted at the Muhammadiyah University Maharesigana organization. The subjects in this study were 114 volunteers from Maharesigana. Data analysis was carried out using SEM-PLS with WARP PLS 5 software. In this study it was found that volunteer motivation was not in line with their affective commitment. volunteer satisfaction at work also has a unidirectional relationship in mediating the influence of volunteer motivation on affective commitment